2022
DOI: 10.3389/fenvs.2022.834055
|View full text |Cite
|
Sign up to set email alerts
|

On-Farm Relationships Between Agricultural Practices and Annual Changes in Organic Carbon Content at a Regional Scale

Abstract: Both soil quality degradation and climate change mitigation issues emphasize the need to increase, or at least stabilize, the topsoil organic carbon content (wt%) in arable land. This on-farm study aimed at measuring the impact of agricultural practices on changes in soil organic carbon (SOC) content over 10 years. A total of 120 fields belonging to 120 farms representative of the cropping systems and soil properties in Western Switzerland (Lake Geneva region) was randomly selected. The field 0–20 cm topsoil w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 65 publications
0
8
0
1
Order By: Relevance
“…Unlike Li et al (2022), Ren et al (2022), and Yew et al (2022), it has been demonstrated that high technologies (Big Data and AI) can (proved by the example of startups in AgroTech) and should be available to small and mediumsized businesses in various sectors of the AI economy. Authors' framework practice-oriented recommendations have been proposed, which are universal and applicable in various sectors of the AI economy, aimed at diffusing high technologies (increasing accessibility) and increasing the efficiency of their use in environmental decision-making in environmental business management.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Unlike Li et al (2022), Ren et al (2022), and Yew et al (2022), it has been demonstrated that high technologies (Big Data and AI) can (proved by the example of startups in AgroTech) and should be available to small and mediumsized businesses in various sectors of the AI economy. Authors' framework practice-oriented recommendations have been proposed, which are universal and applicable in various sectors of the AI economy, aimed at diffusing high technologies (increasing accessibility) and increasing the efficiency of their use in environmental decision-making in environmental business management.…”
Section: Discussionmentioning
confidence: 96%
“…The works of Li et al (2022), Ren et al (2022), and Yew et al (2022) indicate that high technologies require serious financial costs. Therefore, even with the support of the state, these technologies are either inaccessible to small and medium-sized businesses, or dictate the need to optimize costs.…”
Section: Environmental Decision-making In Environmental Business-mana...mentioning
confidence: 99%
See 3 more Smart Citations